Legal Protection for The Customary Law Communities of East Kalimantan Related to Land Control for The National Capital - Fikri Naufal Uyun; Bambang Daru Nugroho; Sari Wahjuni (Program Studi Pendidikan IPS, 2025)
The President of the Republic Indonesia announced the capital’s relocation to East Kalimantan, potentially impacting indigenous communities by threatening their land rights, forests, cultural identity, and traditional rights. The objective of this research is to understand the implementation of land acquisition in the new capital city concerning indigenous land ownership and to analyze the legal protection provided for indigenous communities whose land is used for the capital city’s development. The research method used is normative juridical, employing a descriptive-analytical approach. The research stages involve library research, with data collection conducted through document studies and the review of secondary data relevant to the issues studied. This library research was undertaken to gather primary, secondary, and tertiary legal materials. The data analysis method employed is qualitative juridical analysis. The findings of this study indicate, Land acquisition for the new capital city faces significant challenges in respecting the rights of indigenous communities, despite being legally recognized. In practice, it has not met social aspects, fair compensation, and legal protection. The participation of indigenous communities, such as the Balik Paser Tribe, has been ineffective, and post-dispute compensation is often delayed and insufficient. The legal void regarding compensation for customary land worsens legal uncertainty, potentially violating indigenous rights. A more inclusive, transparent, and fair mechanism is needed to protect their rights.